Impactos nutricionais e produção de pimentão submetido à deficiência hídrica - Lima, Géssica Silva [UNESP]; Broetto, Fernando [UNESP]; Sousa, Antônio De Pádua [UNESP]; Correia, Joselina De Souza [UNESP]; Da Silva, Alexsandro Oliveira (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2016)
The sweet pepper is a solanaceous plant of American origin with large consumption in Brazil. In order to study the effects of water stress on the sweet pepper crop, an experiment was conducted in greenhouse. The treatments consisted of soil water content (100%, 85%, 70% and 55% of moisture in the soil field capacity) in a randomized block design with 6 replicates where the experimental units consisted of 16 plants. During the experiment (47, 62, 77 and 92 days after planting) levels of macronutrients (N, P, K, Ca, Mg and S) and micronutrients (B, Cu, Fe, Mn and Zn) present in each plant fraction and the dry mass of plants for the accumulation of these determination were determined. At harvest the number, width and length of fruits from each plant were obtained. Variables were subjected to Tukey test at 5% probability. The water content in the soil interfered significantly with productive variables. To the accumulation of nutrients in the dry matter (leaf + stem) the elements with higher absorption are ordered as follows: K> N> Ca> Mg> S> P and Fe>Mn> Zn> B> Cu.
Nutritional impacts and production of sweet pepper under water deficit
Keywords: Capsicum annuum L; Management of irrigation; Water demand